Survival rate of implants performed at sites of previously failed implants and factors associated with failure: A retrospective investigation - Georgios S. Chatzopoulos; Larry F. Wolff (Elsevier, 2024)
Background/purpose: Although reimplantation is currently a common treatment procedure, little information on reimplantation success or failure is available in the literature. The purpose of the present investigation was to evaluate the survival rate of dental implants that were performed in sites of previously failed implants and identify factors associated with the treatment outcome. Materials and methods: This retrospective study is based on a cohort of patients rehabilitated with dental implants in the dental clinics of the universities contributing data to the BigMouth network between 2011 and 2022. Implants replacing a previously failed implant at the same site were included. Cases of first and second reimplantations were included Information regarding patients' characteristics including age, gender, ethnicity, race, tobacco use, and systemic medical conditions were extracted from patients' files. Results: Records of 50,333 dental implants placed in 20,842 patients over a 12-year period were screened. Three hundred seventy implants placed in 284 patients were replaced by another implant at the same site. The cumulative survival rates of implants inserted for the first time was 98.6 %, for the first replacements was 96.1 % and for the second replacements was 91.7 %. First reimplants exhibited a significantly higher risk of failure than initial implantation (P < 0.001). Similarly, second reimplants demonstrated significantly greater risk of failure (P = 0.05) when compared to initial implants. No significant associations were detected between replaced implant failures with any of the patient related parameters evaluated (P > 0.05). Conclusion: Within the limitations of the present study, dental implants replacing failed implants exhibited lower survival rates than the rates reported for the previous attempts of implant placement. No risk indicators for implant failure were identified. Additional factors should be examined in future studies.